Single ring isolation of pulmonary veins combined with electrical isolation of the superior vena cava in patients with paroxysmal atrial fibrillation - Li, Xi; Chen, Yanhong; Chen, Guanghui; Deng, Chengang; Tang, Chen; Zhang, Jinlin (Frontiers in Cardiovascular Medicine, 2023)
Background: Atrial fibrillation ablation using single ring isolation of pulmonary veins has been reported. The use of single ring isolation of the pulmonary veins combined with electrical isolation of the superior vena cava has been less frequently reported for patients with paroxysmal AF. Objective: This study aimed to investigate the efficacy and safety of a new ablation strategy for paroxysmal atrial fibrillation: single ring pulmonary vein isolation (SRPVI) of the pulmonary veins combined with electrical isolation of the superior vena cava (SVC). Methods and Results: Sixty consecutive patients with paroxysmal atrial fibrillation from November 2019 to December 2020 were enrolled. The average age of these patients was （55±9） years, 41 were male and 19 were female. Single ring isolation of the pulmonary veins along with electrical isolation of the superior vena cava was completed under AI-guided high-power ablation. One patient had ischemic stroke after the operation, who recovered without severe morbidity after medical treatment. The average follow-up period was (20±7) months. During the follow-up, the success rate, defined as free of >30s of AF/AT, was 91.7%. Five patients had recurrence of AT/AF and 2/5 patients underwent re-do ablation. Conclusion: Our novel ablation strategy: single ring isolation of the pulmonary vein combined with electrical isolation of the superior vena cava in patients with paroxysmal AF is safe and feasible, with acceptable success rate.